1980
DOI: 10.1002/ijc.2910250103
|View full text |Cite
|
Sign up to set email alerts
|

Association of depressed postoperative lymphoproliferative responses to alloantigens with poor prognosis in patients with stage I lung cancer

Abstract: Thirty-five patients with Stage I carcinoma of the lung were tested postoperatively to assess lymphoproliferative responses. Depressed lymphocyte proliferation (LP) responses to alloantaigen in the mixed leukocyte culture (MLC) as measured by thee relative proliferation index (RPI) were associated with a significantly shorter disease-free interval. In this group of patients, the immunologic responses predicted subsequent clinical course better than the TNM classification or the histological type of the tumor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
(22 reference statements)
1
12
0
Order By: Relevance
“…Defective cell-mediated immunity is known to corre late with the extent and spread of tumor in other human malignancies [4,6,13,20], This study confirms that spe cific immunologic mechanisms in patients with RCC remain well at an early tumor stage and reveal attenua tion with metastatic tumor spread. In our study all patients of the different subgroups showed similar levels of NK cell activity, which roughly correlated with the course of the RCC disease.…”
Section: Discussionsupporting
confidence: 72%
“…Defective cell-mediated immunity is known to corre late with the extent and spread of tumor in other human malignancies [4,6,13,20], This study confirms that spe cific immunologic mechanisms in patients with RCC remain well at an early tumor stage and reveal attenua tion with metastatic tumor spread. In our study all patients of the different subgroups showed similar levels of NK cell activity, which roughly correlated with the course of the RCC disease.…”
Section: Discussionsupporting
confidence: 72%
“…In a previous study of Stage I lung cancer patients (Cannon et al, 19806), we have shown that depressed MLC reactivity was associated with a significantly shorter disease-free interval.…”
mentioning
confidence: 88%
“…The data for PHA and MLC responses were expressed as a relative proliferation index (RPI), which is a ratio of the net counts/min (CPM) (CPM in experimental group -CPM in unstimulated control) of a test individual to the mean net CPM in three or more normal individuals tested simultaneously [3]. Depressed or normal responses were determined from cut-off values (< 0.61 for PHA and <_ 0.50 for MLC) set at the lower tenth percentile of a large number (> 1,000) of normal individuals tested in our laboratory [1,3].…”
Section: Assays Rosettes With Sheep Erythrocytes (E) Total Rosette-fmentioning
confidence: 99%